2012
DOI: 10.1097/fpc.0b013e3283527c1c
|View full text |Cite
|
Sign up to set email alerts
|

CYP2A6 and CYP2B6 genetic variation and its association with nicotine metabolism in South Western Alaska Native people

Abstract: Objectives Alaska Native people (AN) have a high prevalence of tobacco use and associated morbidity and mortality when compared to the general U.S. population. Variation in the CYP2A6 and CYP2B6 genes, encoding enzymes responsible for nicotine metabolic inactivation and procarcinogen activation, has not been characterized in AN and may contribute to the increased risk. Methods AN people (n = 400) residing in the Bristol Bay region of South Western Alaska were recruited for a cross-sectional study on tobacco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 60 publications
7
73
0
Order By: Relevance
“…Helen et al, 2012), Caucasians were more likely to be normal metabolizers of nicotine, compared to African Americans. These findings are consistent with previous studies showing that the frequency of CYP2A6 alleles, which influence variability in nicotine metabolism, vary across racial/ethnic groups (Binnington et al, 2012; Nakajima et al, 2006). Likewise, the present study showed that women and African Americans report higher levels of nicotine dependence, however this result was confined to the use of the TTFC measure of nicotine dependence.…”
Section: Discussionsupporting
confidence: 93%
“…Helen et al, 2012), Caucasians were more likely to be normal metabolizers of nicotine, compared to African Americans. These findings are consistent with previous studies showing that the frequency of CYP2A6 alleles, which influence variability in nicotine metabolism, vary across racial/ethnic groups (Binnington et al, 2012; Nakajima et al, 2006). Likewise, the present study showed that women and African Americans report higher levels of nicotine dependence, however this result was confined to the use of the TTFC measure of nicotine dependence.…”
Section: Discussionsupporting
confidence: 93%
“…Research has demonstrated that dual- and multi-product tobacco users experience lower cessation rates [17,18], possibly due to greater cotinine and dependence levels [50]. On average, AN smokers living in Bristol Bay smoke about half as many cigarettes (7.8) per day [42] as US smokers (14.2) [51], but demonstrate similar plasma cotinine levels (170 ng/mL and 200 ng/mL, respectively), suggesting altered nicotine metabolism [49,52]. These changes in nicotine pharmacokinetics imply the need for a increased dosing of nicotine replacement therapy to aid in smoking cessation, a need that may extend to other AN populations, such as those in the Y-K or Norton Sound regions.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of CYP2B6 to nicotine clearance in humans is believed to be relatively small and influenced by the activity of the more dominant CYP2A6 (Yamanaka et al, 2004;Dicke et al, 2005;Al Koudsi and Tyndale, 2010). The impact of CYP2B6 genetic polymorphisms on nicotine clearance has been examined in a number of studies, yielding positive results in some (Johnstone et al, 2006;Ring et al, 2007;Bloom et al, 2013), but not in others (Lee et al, 2007;Binnington et al, 2012). Here, we have provided in vivo proof-ofprinciple in the mouse model that CYP2B6 could make a significant contribution to nicotine oxidation and systemic clearance, particularly at the induced level, albeit in the absence of the more dominant mouse CYP2A5 and CYP2B enzymes.…”
Section: Discussionmentioning
confidence: 99%